A simple model of brain circulation - Nicolas Schmitt; Antoine Soubeyran (Center for Economic Studies and ifo Institute (CESifo), 2005)
This paper considers the allocation of two types of individuals differentiated by levels of talent within and between two countries when they choose to be workers or entrepreneurs. The equilibrium with international migrations requires both countries to be sufficiently different in talent endowments and is consistent with individuals moving in one or in both directions whether they are entrepreneurs or workers. Average welfare per capita falls in the country losing highly talented individuals and rises in the country attracting them. However, in both countries, the liberalization of migrations for immigrants, emigrants or both is always supported by majority voting.
Keywords: F22; F2; J61; 330; Internationale Wanderung; Zwei-Länder-Modell; Brain Drain; Wohlfahrtseffekt; Migrationspolitik; Public Choice; Theorie